LAW AND EDUCATION: THE PRINCIPLE OF FRATERNITY AS A BASIS IN FIGHTING SCHOOL BULLYING AND CIBERBULLYING (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work approached the law and the education as instruments of integration in the search of the effectiveness of the fight against the bullying and the cyberbullying, bringing as base of this confrontation the Principle of the Fraternity as a solution of this social problem, the recognition of equal dignity to all people embodied in the Brazilian Federal Constitution, as well as the objective of building a fraternal society, plural and without prejudice. Thus, the foundation for the revitalization of the Fraternity Principle is evidenced in various constitutional provisions and that equality itself is only possible through the recognition of the other, without implying the cancellation of differences, on the contrary, with the acceptance of differences for reconstruction. of a fraternal society, presented as a resolution for the awareness and prevention of conflicts within schools and in the fight against the systematic intimidation that the Law established as a duty to all society. Awareness of the Fraternity Principle as well as Human Rights should go beyond resolving conflicts of violence through conventional instruments, as violence is not the only form of bullying. Therefore, there is a need for legal and educational awareness in order to stop such conflicts.